ҚАРАҚАЛПАҚСТАН ОЙКОНИМЛЕРИНДЕ САНЛАРДЫҢ ҚОЛЛАНЫЛЫЎЫ МӘСЕЛЕСИ - Қурбанов, М.Д. (FAN va JAMIYAT, 2021)
The article analyzes the use of numbers and semantic features in onomastic materials. In particular, the use of numbers, lexical and symbolic signs in the structure of oikonyms is studied in detail. The opinions of the Turkic scholars are also given. Studies on this topic are also mentioned in the Karakalpak toponymy. The importance of the subject of research for a number of fields of science is explained.